The role of nurse plants in the vegetation dynamics of the succulent Karoo - Beukman, Ruth Pam (Department of Biological Sciences, 2016)
Little is known about the vegetation dynamics of the Karoo region of South Africa. The aim of this study was to focus on the role of the "availability of suitable space" in the regeneration of Succulent Karoo vegetation. By undertaking a series of manipulative experimental transplants and pattern analyses, it was shown not only that shrubs in the Karoo facilitate other species by provision of 'sui table space' beneath their canopies, but also that certain shrub species are more effective "nurses" I than others . The plants dependent on nurse plants are referred to as "patient" plants. Not only did the 'main patient species Tylecodon wallichi require nurse plants generally for successful establishment, but this species was also most successful (in terms of reaching maturity) beneath a specific nurse Pteronia pallens. Thus the patient was "nurse specific". In time however, the initial commensal relationship between the nurse and the patient (whereby the patient benefits and the nurse is unaffected) changes to a competitive one, since nurse vigour declines as the patient grows larger. Despite this area being arid, a manipulative experimental investigation revealed that competition between the nurse and the patient was not for water. An examination of the rooting patterns of the two species showed that their root systems were separated in vertical and horizontal space. Though the mechanism of competition between Pteronia and Tylecodon was not resolved in this study, the patient Tylecodon did appear to reduce nurse vigour and ultimately replace the nurse Pteronia pallens. Since specific species associations do exist (i.e. some patient species are nurse specific), the replacement of one species by another (the nurse by its patient) is predictable and so 'succession' at the scale of the individual plant can be said to occur in the Karoo.